Coulomb Interaction Effects on Pion Production in Au+Au Collisions at Relativistic Energies - Catalin Ristea; Oana Ristea; Alexandru Jipa (Advances in High Energy Physics, 2018)
Coulomb effects on charged pion transverse momentum spectra measured in Au+Au collisions at RHIC-BES energies are investigated. From these spectra the π-/π+ ratios as a function of transverse momentum are obtained and used to extract the “Coulomb kick”, pc (a momentum change due to the Coulomb interaction), and initial pion ratio for three different collision energies and various centrality classes. The Coulomb kick shows a decrease with the increase of beam energy and a clear centrality dependence, with larger values for the most central collisions. The results are connected with the kinetic freeze-out dynamics.